Analisis dan Perancangan Sistem Penentuan Prioritas Penanganan Kerusakan Pipa Air Minum Perusahaan XYZ dengan Metode TOPSIS - Wina Witanti; Tati Harihayati M; Ayu Peraiyantika (LPPM STMIK AMIK BANDUNG, 2022)
XYZ Company is a company that provides drinking water services or Drinking Water Supply System (SPAM) with the type of pipe network SPAM to ensure the certainty of the quantity and quality of drinking water produced and the continuity of drinking water flow. The Operations and Maintenance Department at XYZ company almost every day gets four to six reports of damage to drinking water pipes from customers, while the number of field officers every day is quite limited, namely only two officers who are directly responsible for handling water pipe damage. The Head of the Operations and Maintenance Division had some difficulty in determining which damage reports should be prioritized for field officers to handle. Thus, this study aims to provide an overview to the Head of Operations and Maintenance in determining reports of damage to drinking water pipes that must be prioritized to be handled first. This research will use structured modeling using the Technique For Others Reference by Similarity to Ideal Solution (TOPSIS) with criteria that have been determined by company XYZ.